The Inhibitory Effect of Grasshopper’s Cyperus (Cyperus iria L.) on the Seedling Growth of Five Malaysian Rice Varieties - B. S. Ismail,; Mohammed Abu Bakar Siddique, (Tropical Life Sciences Research, 2011)
Experiments were carried out in the laboratory and greenhouse to determine the growth inhibitory effects of Grassohopper’s cyperus (Cyperus iria L.) on the seedlings of 5 Malaysian rice varieties namely MR211, MRQ74, MR220, MR84 and MR232. Three concentrations of the aqueous extract of the weed (12.5, 25.0 and 50.0 g/l) and weed debris (5, 10 and 20 g dry debris/1000 g soil) were used to test the allelopathic effect of C. iria on the growth of the rice plants. The weed leaf, stem and root extracts reduced the growth of the rice seedlings and showed selective activity in the varieties. The C. iria leaf and stem extracts showed comparatively higher growth inhibitory effects than those from the root. The weed extract caused more reduction in the root length of the rice plant compared to the shoot length. Among the rice varieties tested, MR232 was found to be more susceptible to the weed inhibitory effect. The leaf extract of C. iria at full strength caused root and shoot reduction of MR232 by 88.1% and 73.1% respectively (compared to the control). In most cases the fresh weight of the rice seedlings were more affected than the plant height. Weed debris caused significant reduction of leaf chlorophyll content in all the rice varieties tested with the exception of MR211. The chlorophyll content of MR232 was greatly affected by the weed debris which caused reduction of 36.4% compared to the control. The inhibitory effects of weed extracts and debris on rice growth parameters were found to be concentration dependent. Kajian telah dijalankan di dalam makmal dan rumah hijau bagi menentukan kesan perencatan pertumbuhan Cyperus iria pada anak benih bagi 5 varieti padi Malaysia iaitu MR211, MRQ74, MR220, MR84 dan MR232. Tiga kepekatan ekstrak akues rumpai (12.5, 25.0 dan 50.0 g/l) dan sarap rumpai (5, 10 dan 20 g sarap kering/1000 g tanah) telah digunakan bagi menguji kesan alelopati bagi C. iria pada pertumbuhan pokok padi. Ekstrak daun, batang dan akar rumpai merencat pertumbuhan anak benih padi dan menunjukkan aktiviti memilih bagi semua varieti. Ekstrak daun dan batang C. iria menunjukkan kesan perencatan pertumbuhan yang tinggi berbanding dengan ekstrak akar. Ekstrak rumpai menyebabkan pengurangan yang lebih terhadap panjang akar berbanding dengan panjang pucuk bagi pokok padi. Di antara varieti padi yang diuji, didapati C. iria lebih memberikan kesan perencatan kepada MR232. Ekstrak C. iria pada kepekatan tertinggi menyebabkan pengurangan pada MR232 sebanyak 88.1% dan 73.1% pada akar dan pucuk masing-masing (perbandingan dengan kawalan). Di dalam kebanyakan kes, berat segar bagi anak benih padi lebih banyak dipengaruhi oleh ketinggian pokok. Sarap rumpai menyebabkan pengurangan yang signifikan bagi kandungan klorofil daun bagi semua varieti beras yang diuji kecuali pada MR211. Kandungan klorofil bagi MR232 sangat dipengaruhi oleh sarap rumpai yang menyebabkan pengurangan sebanyak 36.4% berbanding dengan kawalan. Kesan perencatan bagi ekstrak rumpai dan sarapnya kepada parameter pertumbuhan padi didapati bergantung kepada kepekatan.